Restoring soil health to reduce irrigation demand and buffer the impacts of drought - Rebecca SCHNEIDER, Stephen MORREALE, Zhigang LI, Erin MENZIES PLUER, Kirsten KURTZ, Xilu NI, Cuiping WANG, Changxiao LI, Harold VAN ES (Frontiers of Agricultural Science and Engineering, 2020)
Irrigation consumes three quarters of global water withdrawals each year. Strategies are needed to reduce irrigation water use, including increasing the efficiency of transfer methods and field application. Comprehensive restoration of soil health, specifically through organic matter amendments, can substantially reduce irrigation demand and increase crop yield. A program to restore severely degraded and desertified soils by incorporating coarse woodchips into the soil successfully increased rainfall capture and elevated soil moisture for several weeks between rainfall events at both Ningxia, north-west China and North Dakota, USA. With addition of fertilizer, woodchip incorporation further increased growth of wheat and alfalfa. Comprehensive soil health assessment of remnant grasslands was used to develop target reference soil profiles by which to guide restoration efforts. Given that most agricultural soils are degraded to some degree, soil health restoration can provide a powerful strategy toward achieving global food and water security.